2004
DOI: 10.1121/1.1757454
|View full text |Cite
|
Sign up to set email alerts
|

Specification of cross-modal source information in isolated kinematic displays of speech

Abstract: Information about the acoustic properties of a talker's voice is available in optical displays of speech, and vice versa, as evidenced by perceivers' ability to match faces and voices based on vocal identity. The present investigation used point-light displays (PLDs) of visual speech and sinewave replicas of auditory speech in a cross-modal matching task to assess perceivers' ability to match faces and voices under conditions when only isolated kinematic information about vocal tract articulation was available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
58
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 36 publications
11
58
1
Order By: Relevance
“…In fact, initial support for this prediction has been provided by four very recent articles reporting research conducted in parallel with our own study (discussed below; Kamachi, Hill, Lander, & Vatikiotis-Bateson, 2003;Lachs & Pisoni, 2004a, 2004b, 2004c. These four articles reported that, with an XAB methodology, observers were able to successfully match voices to faces and faces to voices.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…In fact, initial support for this prediction has been provided by four very recent articles reporting research conducted in parallel with our own study (discussed below; Kamachi, Hill, Lander, & Vatikiotis-Bateson, 2003;Lachs & Pisoni, 2004a, 2004b, 2004c. These four articles reported that, with an XAB methodology, observers were able to successfully match voices to faces and faces to voices.…”
mentioning
confidence: 55%
“…These auditory tests involved either deleting the phonetically extraneous information from the signal (e.g., sine wave speech; Kamachi et al, 2003;Lachs & Pisoni, 2004b, 2004c or testing whether acoustic distortions that hinder phonetic perception also hinder cross-modal matching (Lachs & Pisoni, 2004a). The results of these tests support the conclusion that the idiosyncratic phonetic information contained in the auditory signal is salient for cross-modal matching.…”
mentioning
confidence: 97%
See 3 more Smart Citations